Productivity Performance of the Village Government in Population Administration Services - Muhammad Royan; Lailatul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2021)
As in Law Number 6 of 2014 it seeks to restore the concept, and form of the Village as it came from, the Village or called by another name, is a legal community unit that has the authority to regulate and manage the interests of the local community based on their origins and customs. local customs that are recognized in the national government system and are located in the Regency Area. Villages can be formed, deleted, and/or merged with due regard to their origin at the initiative of the community with the approval of the Regency Government and DPRD. Substantively this Village Law implies an effort to empower village government officials and also village communities. The Village Government or in the form of another name such as the Marga Government, its existence is in direct contact with the community, as the spearhead of the leading government. The implementation of village autonomy which is characterized by good service can provide satisfaction for people in need because it is fast, easy, precise and at an affordable cost, therefore implementation in the field must be supported by the factors involved in implementing the policy on the village. The officer's perception of his work depends on the level of intrinsic and extrinsic outcomes and how the worker/employee views the outcome and reflects his attitude towards his job. Mental attitude is a mental condition that encourages a person to try to achieve maximum work potential. The performance of the Tawang Rejeni village government has not been good enough in productivity, this can be seen from the mental attitude and behavior of village officials in managing certificates to the community.